Canine mast cell tumours: decision‐making and treatment. Issue 7 (16th July 2015) - Warland, James; Brioschi, Valentina; Owen, Laura; Dobson, Jane
Abstract : Mast cell tumours (MCTs) are common tumours in dogs. They mainly affect the skin, although they can affect other tissues and organs. In recent years, there have been significant advances in predicting skin MCT behaviour and treatment, including the licensing of two tyrosine kinase inhibitors for the treatment of this condition. This article focuses on skin (cutaneous and subcutaneous) MCTs. It summarises current understanding of MCT behaviour, prognosis and treatment, with a particular focus on treatment decision‐making.